The Equation on the Justice for Migrant workers: The Urgency of Protection on Prevention Smuggled Migrant worker based on Indonesian laws - Narwastuty, Dian; Sirait, Yohanes Hermanto; Alim R, Kevin (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2021)
Indonesia’s marine territory has become a big challenge for the Government of Indonesia to manage it. Nowadays, Indonesian marine has lot of regulation in the sea. But it’s cannot prevent the basic interest of all people that earnings life from there. A lot of migrant has been smuggled in and by Indonesian’s marine territory. The main concerns that arouse are: how should government give an equation for Indonesian migrant workers that are smuggled and how should the government put migrant workers protection to supply the equation for them. These questions will solve by a normative juridical study on the protection of natural resources and the resources of Indonesian fisherman. The study uses normative legal research which elaborated with conceptual approach from numbers of regulations that apply in marine labor law and employment law. This research is also complemented by a literature approach in the form of Indonesian legal literature and marine journals to address the issues raised in this paper. The findings in practice prove that the government should give more attention for the fisherman’s welfare and protection related to fish catching. The objective protection for Indonesian marine resources is from regulated all the regulation to develop Indonesia economic from Maritime sector. It is all needed to make a new system in legal protection for Fisherman and Marine Resources in Indonesia.